Test-retest reliability of transport-related physical activity performed during the lifetime - Boyle, Terry; Heyworth, J.; Bull, F.; Fritschi, L. (Human Kinetics, Inc, 2013)
BACKGROUND: One of the convenient ways to achieve recommended levels of physical activity is through 'active transport,' such as walking or cycling to and from work or school. Although studies have shown that participants can reliably recall information about recent transport-related physical activity, it is not known if the reliability remains high when asking about lifetime behavior. This study tested the reliability of questions that collect information about transport-related physical activity performed over the lifetime. METHODS: Participants were asked to complete self-administered questions about transport-related physical activity on 2 separate occasions. The questions asked about cycling and walking to and from work and/or school during 3 age periods: 15-24 years, 25-39 years, and 40 years and above. A lifetime average was also calculated for cycling, walking, and total activity. RESULTS: There was fair to good test-retest reliability of the age-period specific questions for transport-related cycling (ICCs from 0.65-0.74), walking (ICCs from 0.44-0.58), and total activity (ICCs from 0.57-0.66). The reliability of the lifetime averages were also fair to good (ICCs from 0.58-0.70). CONCLUSIONS: The questions tested in this study have moderate reliability, and appear to be useful questions for measuring lifetime transport-related physical activity.